2- (3,5-Di-tert-butyl-4-hydroxybenzyl) sulfanyl benzoic acid - Alhadi, A.A.; Olmstead, M.M.; Ali, Hapipah Mohd; Khaledi, H. (International Union of Crystallography, 2010)
In the title compound, C(22)H(28)O(3)S, the dihedral angle between the two aromatic rings is 80.56 (6)degrees. The hydroxy group is shielded by the two sterically hindered tert-butyl groups and therefore is not involved in any hydrogen bonding. The C-O-H fragment is coplanar with the aromatic ring, the dihedral angle between them being 7(5)degrees. In the crystal structure, pairs of molecules are hydrogen bonded across crystallographic centers of symmetry.